2004
DOI: 10.1007/978-3-0348-7934-7
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial Identity Rings

Abstract: verzeichnet diese Publikation in der Deutschen Nationalbibliografie; detaillierte bibliografische Daten sind im Internet über abrufbar. This work is subject to copyright. All rights are reserved, whether the whole or part of the material is concerned, specifically the rights of translation, reprinting, re-use of illustrations, recitation, broadcasting, reproduction on microfilms or in other ways, and storage in data banks. For any kind of use permission of the copyright owner must be obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 0 publications
1
76
0
5
Order By: Relevance
“…The proof, however, is somewhat involved, and will not be elaborated here. We direct the interested reader to Chapter 6 of [1])…”
Section: Introductionmentioning
confidence: 99%
“…The proof, however, is somewhat involved, and will not be elaborated here. We direct the interested reader to Chapter 6 of [1])…”
Section: Introductionmentioning
confidence: 99%
“…Consider the natural GL n -action on the space V = M r n of r-tuples of n×n-matrices by simultaneous conjugation. The variety X = M r n // GL n has been extensively studied in the context of both invariant and PI theories; an overview of this research area can be found in [6], [21] or [5]. In [22,23] the second author constructed a large family of automorphisms of X = V // PGL n (for r n + 1).…”
Section: Then the Luna Stratification In V // G Is Intrinsic Moreovementioning
confidence: 99%
“…Important properties of matrix operations are often expressed in form of laws or identities such as the associative law for multiplication of matrices. Studying matrix identities that involve multiplication and addition is a classic research direction that was motivated by several important problems in geometry and algebra (see [1] for a survey of the origins of the theory) and that has eventually led to the profound and beautiful theory of PI-rings [14,21,23,47]. Matrix identities involving along with multiplication and addition also certain involution operations (such as taking the usual or symplectic transpose of a matrix) have attracted much attention as well, see, for instance, [9,10,15,20,47].…”
Section: Matricesmentioning
confidence: 99%